Vocatinal training and Job placement. Reflections about Labour Market - José Manuel MUÑOZ RODRÍGUEZ (Ediciones Universidad de Salamanca, 2009)
Connection between training systems and labour market is not easy and not obvious. Although demands of labour market can be responsibility of training systems, in fact, reality does not show this, due to relationship between both is not clear. This paper exposes some notes about labour market and training systems. Then, we present several measures aimed at increasing labour insertion by social and educative politics.